The Effect of Feed Fermented Rubber Seeds with Rhizopus oligosporus and Neurospora stiophila on the Percentage of Abdominal Fat and Blood Profile of Native Chickens - Dadik Pantaya; Suci Wulandari; Alditya Putri Yulinarsari; Holilul Rohman; Qorina Insani Aulia Rizqi; Moch. Ibnaq Uzaman (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
The purpose of this study was to explore feed ingredients from rubber seed plantation waste and their effect on the percentage of abdominal fat and blood profile due to the high content of rubber seed oil and the presence of anti-nutrients (HCN). The concentrations of Rhizopus oligosporus and Neurospora stiophila inoculum were 109 CFU/g each. This study was subjected to a Nested Completely Randomized Design. The first factor was the type of microbial used. Factor II was inoculum dose (0%, 0.4%, 0.8%, 1.6%, and 3.2%). The best concentration of inoculum was used in the making of fermented rubber seeds to be given to native chickens. The application on native chickens used statistical analysis Completely Randomized Design consisting of 3 treatments, namely P1: feed without using fermented rubber seeds; P2: feed using 5% Neurospora fermented rubber seed; and P3: feed using 5% Rhizopus fermented rubber seed. Significantly different results continued with Duncan's test. The results showed that the type of fungi had no significant effect on the treatment, but increasing the dose of fungi inoculum up to 3.2% had a significant effect on decreasing the content of dry matter, HCN, and crude fiber in rubber seeds. Administration of Rhizopus and Neurospora inoculums had a significant effect on increasing abdominal fat when compared to control. The conclusion of this study was that the processing method before fermentation and the amount of fungal inoculum used during fermentation affected the nutritional and antinutritional content of HCN rubber seeds. The presence of fermented rubber seeds which had either Rhizopus oligosporus or Neurospora stiophila increased the percentage of abdominal fat. Native chickens which were given fermented rubber seeds with Neurospora showed a higher level of stress marked by increased blood lymphocytes